Peran Manajemen Sumber Daya Manusia Perusahaan dan Industri dalam Pencegahan Korupsi - Ninawati, NINAWATI (Media Nusantara, 2022)
Corruption by employees in business and industry occurs for the following reasons: (1) There are economic incentives for workers whose wages are low and there is an urgent need for workers. (2) There is encouragement from the organization/department to emphasize that corruption is not a harmful act (corruption is a normal phenomenon). Therefore, the company’s human resource management plays an important role in preventing corruption. If possible, industrial organizations/companies should implement talent development programs designed using methodologies that can transform talent’s knowledge, skills, expertise, attitudes, and behaviors. Therefore, it is necessary to make efforts to develop the capacity of every human resource in the industry so that it has a positive impact on capacity building, institutional strengthening and system strengthening. Employee ability is the ability of someone who works in an industrial organization, especially an industrial company, to carry out their duties and functions, as well as the ability to achieve their goals effectively and efficiently.